Vein of Galen Aneurysmal Malformation: Advances in Management and Endovascular treatment. Issue 2 (1st June 2018) - Berenstein, Alejandro; Paramasivam, Srinivasan; Sorscher, Michelle; Molofsky, Walter; Meila, Dan; Ghatan, Saadi
Abstract: BACKGROUND: Vein of Galen aneurysmal malformation (VGAM) is a rare congenital vascular malformation representing <1% of all arteriovenous malformations. The knowledge and strategies in the management are constantly evolving. OBJECTIVE: To review our series of postneonatal VGAM patients treated over 11-yr period. METHODS: Retrospective analysis of 113 VGAM treated between January 2004 and April 2015. After exclusions, 45 patients were included: 33 choroidal and 12 mural types. RESULTS: Presenting symptom in the order of frequency: enlarged head circumference, antenatal diagnosis, mild CHF, and PHT at birth. Older patients were diagnosed following trauma, headache, cognitive decline, and incidentally during workup for other diseases. Hydrocephalus due to hydrodynamic disorder was present in 70% of choroidal and 58% of mural types. Only a quarter needed cerebrospinal fluid diversion procedure. Radiological cure was achieved in 82%; the outcome graded on a 5-point scale: 0 (death) to 4 (normal). A total of 66.6% are neurologically and developmentally intact with outcome score 4, 20% had outcome score of 3, and 8.9% had outcome score of 2. There was 4.4% mortality. Dural feeders to VGAM were found either in the initial or during the treatment in 22.2% in the current series. Angiogenesis from pial vessels developed after partial embolization in 17.7% that resolved completely following complete obliteration of VGAM. CONCLUSION: Technical and technological advancements in endovascular embolization along with better understanding of clinical, anatomic, and pathophysiological aspects have resulted in significantly improved outcome and prognosis in VGAM. Most patients with proper treatment can now survive and most develop normally following appropriately timed treatment.